2006
DOI: 10.1291/hypres.29.123
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Vardenafil Therapy Improves Hemodynamics in Patients with Pulmonary Hypertension

Abstract: The phosphodiesterase-5 (PDE-5) inhibitor, sildenafil, has been reported to produce sustained pulmonary vasodilatation in patients with pulmonary hypertension (PH). Recently, vardenafil, a more potent and selective PDE-5 inhibitor than sildenafil, has been approved for the treatment of erectile dysfunction. However, the long-term effects of oral vardenafil in patients with PH are unknown. We studied five consecutive patients with PH; one with primary pulmonary hypertension, two with chronic pulmonary thromboem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 32 publications
3
19
0
1
Order By: Relevance
“…In some clinical studies it is reported that the clinical efficacy of treatment with sildenafil monotherapy or combination therapy in patients with pulmonary hypertension [40,41]. We need to perform additional studies treated with higher dose of sildenafil in monocrotaline-induced pulmonary hypertensive rats, including new phosphodiesterase type V inhibitors, tadalafil [42] and valdenafil [43]. Further experiments using additional doses of sildenafil and comparison of properties with other phosphoesterase inhibitors would help to clarify this issue.…”
Section: Discussionmentioning
confidence: 99%
“…In some clinical studies it is reported that the clinical efficacy of treatment with sildenafil monotherapy or combination therapy in patients with pulmonary hypertension [40,41]. We need to perform additional studies treated with higher dose of sildenafil in monocrotaline-induced pulmonary hypertensive rats, including new phosphodiesterase type V inhibitors, tadalafil [42] and valdenafil [43]. Further experiments using additional doses of sildenafil and comparison of properties with other phosphoesterase inhibitors would help to clarify this issue.…”
Section: Discussionmentioning
confidence: 99%
“…Ghofrani et al 51 demonstrated the importance of studying each drug's specific effect on cardiovascular diseases, given their differences on various hemodynamic parameters. Aizawa et al 52 confirmed Ghofrani et al's 51 finding that vardenafil is not specific to the pulmonary vasculature in the acute setting, but with chronic treatment, only the pulmonary artery pressure and PVR were decreased. The case studies have demonstrated the potential role of tadalafil in patients with severe pulmonary hypertension.…”
Section: Role Of Pde-5 Inhibitors In Pulmonary Hypertensionmentioning
confidence: 63%
“…Aizawa et al 52 Vardenafil decreased both PVR and SVR acutely; chronic treatment reduced PVR/SVR ratio in patients with pulmonary hypertension, suggesting a greater effect on PVR.…”
Section: Study Findingsmentioning
confidence: 99%
“…Beş hastadan oluşan seride hastalara 3 ay boyunca günde 3 defa 5 mg vardenafil verilmiş, üçüncü ayda pulmoner arter basıncı ve pulmoner vasküler direncin anlamlı olarak düştüğü görülmüştür. Dünya sağlık örgütü fonksiyonel sınıfı düzelmiş, 6 dakika yürüme testinde değişiklik olmamıştır (10).…”
Section: Vardenafilunclassified